The Influence of Transparency and Village Financial Management and Accountability of Village Fund Allocation in Cikembar District and Warungkiara District, Sukabumi Regency - Maulana, Fahmi Nurilham; Setiawan, Ade Budi; Aziz, Ayi Jamaludin; Triwidatin, Yuppy (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the effect of transparency and village financial management on accountability for village fund allocation in Cikembar District and Warungkiara District, Sukabumi Regency. The population in this study includes 22 villages spread across Cikembar District and Warungkiara District, Sukabumi Regency. Based on the purposive sampling method, 110 respondents were obtained. The research instrument used a questionnaire. Hypothesis testing and research instruments use multiple linear regression analysis tools. Based on the analysis carried out, the results of this research show that transparency and village financial management have a simultaneous and partial effect on accountability for village fund allocation in Cikembar District and Warungkiara District, Sukabumi Regency.